Experimental investigation of axial loaded circular steel tube short columns filled with manufactured sand concrete. (15th October 2020) - Guan, Minsheng; Wei, Chunqing; Wang, Ying; Lai, Zhichao; Xiao, Qian; Du, Hongbiao
Highlights: Experimentally investigates the axial compressive behavior of MS-CFT short columns. Conducts 63 axial compressive tests on MS-CFT short columns. Evaluates the influences of four test parameters. Evaluates the applicability of current design codes for MS-CFT short columns. Abstract: Compared with natural sand, manufactured sand (MS) is more economical and environmentally friendly. This paper experimentally evaluates the axial compressive behavior of circular steel tube short columns filled with manufactured sand concrete (MS-CFT). 63 specimens were designed and tested to study the following test parameters: the source of sand, the content of stone powder, the diameter-to-thickness ratio of steel tube, and the compressive strength of concrete infill. Test results showed that the axial compressive strength of MS-CFT short columns increased with reducing the diameter-to-thickness ratio of steel tube or increasing the compressive strength of concrete infill, but was not appreciably affected by the type of stone used to manufacture the sand or the content of stone powder. Several design codes for conventional CFT columns were used to estimate the axial compressive capacities of the MS-CFT specimens tested in this experimental program to evaluate the applicability of these codes. It was shown that these design codes could provide conservative estimations.